Stand out : five key skills to advance your career - Stevens, Debra (Pearson, 2021)
Debra Stevens is the founder of Dramatic Training Solutions a specialist soft skills training company covering all aspects of communication, behaviour and leadership. Debra has over 25 years of experience working with large companies globally across 6 continents. She has trained 10's of thousands of people in soft skills and has worked with companies such as Coca-Cola, Royal Caribbean Cruise Lines, Royal Bank of Scotland, Pearson Education and Stena Ferries. Her style of training is always immersive, real and human and her coaching is compassionate and honest. She is passionate about helping people find authentic ways to connect with others, which she believes have always been important but will become, essential for survival in the new workplace.